An Empirical Investigation into Measurement and Determinants of Food Security. Issue 6 (3rd June 2018) - Maitra, Chandana; Prasada Rao, D.S.
ABSTRACT: We examine the association between calorie-based indicators and experiential indicators of food security using data from slum households of Kolkata surveyed in 2010–2011. Experiential indicator is constructed following the United States Household Food Security Survey Module. Calorie based indicator is constructed using household-specific calorie norms. Modelling techniques take account of potential endogeneity in the relationship. The two indicators are aligned in the same direction implying more accurate targeting. However, there is a lack of one-to-one correspondence between the two measures and the drivers of calorie deprivation and food insecurity also differ, suggesting a one-size-fits-all policy cannot address both concerns simultaneously.